2010
DOI: 10.1016/j.jvs.2010.06.172
|View full text |Cite
|
Sign up to set email alerts
|

Sodium 4-phenylbutyrate protects against spinal cord ischemia by inhibition of endoplasmic reticulum stress

Abstract: Reduction in ER stress-induced spinal cord injury was achieved by the administration of 4-PBA. 4-PBA may be a strong candidate for use as a therapeutic agent in the treatment of ischemic spinal cord injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(47 citation statements)
references
References 38 publications
3
42
1
1
Order By: Relevance
“…In this context, oligodendrocytes and neuropeptide-secretory neurons are of particular relevance for future studies in order to uncover the mechanisms underlying the impact of the UPR in SCI. In fact, correlative studies suggest that the protection of valproate 11,36 or sodium 4-phenylbutyrate 14 against SCI models is associated with attenuated levels of ER stress markers. The partial improvement obtained after XBP1s gene transfer over a wild-type condition where the UPR is already activated suggests that locomotor improvements can be achieved with treatments of days after damage (considering the delay of 41 week for gene expression after AAV gene transfer).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, oligodendrocytes and neuropeptide-secretory neurons are of particular relevance for future studies in order to uncover the mechanisms underlying the impact of the UPR in SCI. In fact, correlative studies suggest that the protection of valproate 11,36 or sodium 4-phenylbutyrate 14 against SCI models is associated with attenuated levels of ER stress markers. The partial improvement obtained after XBP1s gene transfer over a wild-type condition where the UPR is already activated suggests that locomotor improvements can be achieved with treatments of days after damage (considering the delay of 41 week for gene expression after AAV gene transfer).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, damage to the spinal cord by transient ischemia correlates with increased ER stress levels. 12,14 A recent study indicated that deletion of chop enhances motor recovery after moderate levels of SCI induced by contusion, 13 whereas CHOP deficiency did not have any effect under conditions of severe SCI. 15 As CHOP expression is one of dozens downstream targets of the UPR, 5 and the ATF4/CHOP pathway is activated by a variety on non-ER stress-related stimuli including DNA damage, 16 oxidative stress, 17 metabolic changes, 18 inflammation, among other effects, 19 direct manipulation of proximal UPR components is required to directly define the contribution of ER stress to SCI.…”
mentioning
confidence: 99%
“…The administration of 4-PBA and TUDCA improves insulin sensitivity and glucose homeostasis in liver of mouse models of diabetes and obesity [88], reducing of leptin resistance in mouse obesity model [89]. These compounds have neuroprotective effects in models of brain ischemia-reperfusion [90], HD [91], as well as spinal cord ischemia model [92], among other diseases.…”
Section: Chemical Chaperonesmentioning
confidence: 99%
“…L'administration de chaperons chimiques dans un modĂšle expĂ©rimental d'ischĂ©mie-reperfusion cĂ©rĂ©brale attĂ©nue le stress du RE, en corrĂ©lation avec les effets neuroprotecteurs. Des rĂ©sultats similaires ont Ă©galement Ă©tĂ© publiĂ©s dans des modĂšles expĂ©rimentaux de lĂ©sions de la moelle Ă©piniĂšre et d'altĂ©rations des photorĂ©cepteurs [32]. Les chaperons chimiques protĂšgent Ă©gale-ment le foie de la stĂ©atose et de l'ischĂ©mie associĂ©e au stress du RE [33].…”
Section: Les Agonistes Et Antagonistes De La Clairance Des Protéines unclassified